(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
In the process of drilling production wells, it is important to choose the right type and volume of drilling fluids, the correct choice of well bottom design, not to pollute the productive formation and maintain its natural permeability, and to effectively open the productive formation. Methods and drilling of wells Ensuring long-term production is one of the most pressing issues today.